Longitudinal melanonychia in a child. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Longitudinal melanonichia (LM) may be due to benign (melanocytic hyperfunction, lentigo, nevus) or malignant (melanoma) causes. In the Caucasian prepuberal child a nevus is the most frequent benign cause of LM. There are 11 cases of melanoma in prepuberal age in the world literature; it is always melanoma in situ and many Authors are not sure of the diagnosis. The clinical criteria for differentiating benign from malignant LM in the adult – band width, irregular bands, rapid growth, involvement of nail folds, nail dystrophy – are not valid in the child (1). The matrix biopsy, more difficult in the child and not without side effects, is not always diriment for the peculiarities of the melanocytes of the matrix epidermis. For these reasons, most Authors (1, 2) advise to behave for the child’s LM as for cutaneous melanocytic nevi in pediatric age, suggesting clinical monitoring except for clear signs of malignancy.